2010
DOI: 10.1002/mus.21642
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postsynaptic neuromuscular junction abnormalities in musk myasthenia

Abstract: Autoantibodies to muscle-specific kinase (MuSK) can cause myasthenia gravis (MG). The pathophysiological mechanism remains unknown. We report in vitro electrophysiological and histological studies of the neuromuscular junction in a MuSK MG patient. Low levels of presynaptic acetylcholine release and small miniature endplate potentials were found. This combination of pre-and postsynaptic abnormalities was supported by histology, revealing partially denervated postsynaptic areas, and some degeneration of postsyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 26 publications
(43 reference statements)
1
50
0
1
Order By: Relevance
“…Ultrastructural studies have previously focused on the description of NMJs, offering controversial results: structural integrity of nerve terminals and junctional folds were found in MuSK-MG, while both degeneration and decreased postsynaptic folds have been described with a shorter distance between the postsynaptic membrane and myofibrillar compartment [16,17,19]. In these cases, mitochondria were localized in the subsynaptic space, accumulating directly beneath the postsynaptic membrane, whereas subsynaptic nuclei disappeared.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Ultrastructural studies have previously focused on the description of NMJs, offering controversial results: structural integrity of nerve terminals and junctional folds were found in MuSK-MG, while both degeneration and decreased postsynaptic folds have been described with a shorter distance between the postsynaptic membrane and myofibrillar compartment [16,17,19]. In these cases, mitochondria were localized in the subsynaptic space, accumulating directly beneath the postsynaptic membrane, whereas subsynaptic nuclei disappeared.…”
Section: Discussionmentioning
confidence: 93%
“…The most important mechanism of AChR loss is the complement-mediated damage in the postsynaptic membrane resulting from complement-mediated injury to the endplates with morphological simplification of the postsynaptic folds [16,19]. While MuSK function is essential during the development of the NMJ, its role in the adult muscle is less clear, although it is probably involved in structure maintenance of the postsynaptic membrane [14,17,20]. In addition, it is still not clear how MuSK antibodies cause myasthenic symptoms, and it has even been suggested that they may not be pathogenic [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro microelectrode studies showed a normal EPP decay time constant. 34 In the 3 MuSK-MG patients observed by us, the MEPC decay times were shorter than normal, normal, and 2-fold prolonged 33 compared to controls. Thus, our biopsy findings do not indicate that MuSK-MG patients have endplate AChE deficiency.…”
Section: In Vitro Plate-binding Assay Shows That Musk-igg Blocks Bindmentioning
confidence: 62%
“…Studies have shown alterations in nAChR expression in some conditions including muscle denervation (Roztler and Brenner 1990;Schuetze and Role 1987;Gattenlöhner et al 2002), nerve injury (Ma et al 2007), alterations muscle fiber type composition (Jin et al 2008), relative muscle activity (Roztler and Brenner 1990) and some pathologies such myasthenia gravis and congenital myasthenic syndromes (Kalamida et al 2007). According to Niks et al (2010) abnormalities in the proteins of the dystrophinglycoprotein complex can also influence the NMJ structure changing the functional properties nAChRs modulating the skeletal muscle phenotype (Jin et al 2008).…”
Section: Discussionmentioning
confidence: 99%